Prevalence, risks, and comorbidity of thyroid dysfunction: a cross-sectional epidemiological study - Nearmeen M Rashad; Ghada M Samir (SpringerOpen, 2019)
Background Worldwide, the incidence of individuals with thyroid dysfunction is increasing and represents approximately 30-40% of the patients seen in an endocrine clinic. The undiagnosed thyroid dysfunction may adversely affect the metabolic control and add more risk to already predisposing cardiovascular risk factors. Thus, the objective of the present study was to assess the prevalence of undiagnosed thyroid dysfunction and its association with other comorbidities. Patients and methods A cross-sectional study was conducted on 430 patients who attended the outpatient clinic of Diabetes and Endocrinology, the Internal Medicine Department, Zagazig University Hospitals. All patients underwent clinical and laboratory evaluations. A total of 304 patients had normal thyroid function (euthyroid) and 126 patients had thyroid dysfunction, who were stratified into one of the following groups based on the reference of the normal thyroid function test result: hyperthyroidism, subclinical hyperthyroidism, hypothyroidism, and subclinical hypothyroidism. Thyroid-stimulating hormone and free thyroxine were used as the screening tests to diagnose thyroid dysfunction. Results Our results show the prevalence of thyroid dysfunction was 29.3%. Among thyroid dysfunction groups, the prevalence of subclinical hypothyroidism was 44.4%, hypothyroidism was 20.6%, hyperthyroidism was 19.2%, and subclinical hyperthyroidism was 15.8%. The prevalence of overall thyroid dysfunction among studied patients with type 2 diabetes mellitus was 27.6%, whereas in type 1 diabetes mellitus, the prevalence of overall thyroid dysfunction was 38.7%. Patients with subclinical hypothyroidism and hypothyroidism had a high prevalence of hypertension compared with those with subclinical hyperthyroidism and clinical hyperthyroidism. Approximately 8% of studied pregnant female patients had subclinical hypothyroidism. Among the 15% of female patients in the postpartum period who had thyroid dysfunction, 10% had clinical hypothyroidism and 5% had clinical hyperthyroidism. Among postmenopausal women, 20% had thyroid dysfunction (12% had subclinical hypothyroidism and 8% had clinical hypothyroidism). Conclusion The most frequently undiagnosed thyroid dysfunction was subclinical hypothyroidism. Thyroid dysfunction was common in certain age groups: reproductive age and postmenopausal as well as in patients with diabetes mellitus and hypertension; thus, screening for thyroid disease among those groups of patients should be routinely performed.